Morphology and rheology of composites of poly(styrene-co-2-vinyl pyridine) copolymers and phosphotungstic acid - He, Qingbin; Zhang, Yanjie; Zhang, Zhijie; Qian, Hu-Jun; Chen, Quan (Frontiers in Soft Matter, 2022)
Morphological and rheological properties are examined for poly(styrene-co-2-vinyl pyridine) (P(S-co-2VP)) copolymers upon introducing phosphotungstic acid, one kind of polyoxometalates (POMs). The phosphotungstic acid protonates the 2VP monomers, and the deprotonated phosphotungstic acid effectively crosslinks the protonated 2VP monomers, inducing phase segregation into the S-rich and 2VP-rich domains. Linear viscoelasticity (LVE) of the composite samples strongly relies on the continuity of the 2VP-rich domains and can be classified into the following three types. (1) For 2VP-rich sphere domains in the S-rich matrix, LVE is akin to the conventional elastomer characterized by a wide rubbery regime before the terminal relaxation. (2) For bicontinuous morphology, where both the 2VP-rich and S-rich domains are continuous, two glassy processes manifest in LVE, and the chain relaxation is controlled by the continuous ion dissociation in the less mobilized 2VP-rich domain. (3) When the 2VP-rich domain is the only continuous phase, only the glassy modulus of the 2VP-rich domain manifests in LVE, and the chain relaxation is activated by the continuous ionic dissociations in the matrix. Surprisingly, the relaxation time obtained for all three abovementioned morphologies can be reduced to a universal behavior once the average glass transition temperature of the 2VP-rich region and the number of effective stickers per chain have been properly normalized, indicating that these two parameters control the chain-dimensional dynamics.